161 THE ROLE OF THE GERIATRIC DAY HOSPITAL DURING THE COVID 19 PANDEMIC. (18th November 2021) - Lynch, A; Quinn, L; Briggs, R; Tan, T; Thorpe, O; Romero-Ortuno, R; Byrne, T; Cunningham, C; Lavin, A
Abstract: Background: The geriatric day hospital (GDH) provides outpatient medical, nursing and rehabilitation care to older adults. Historically the main focus has been on rehabilitation. This project's objective was to evaluate how the GDH adapted during the COVID-pandemic to provide acute medical care to older adults. Methods: This is a pre and post COVID-19 comparative study. Referral source, multidisciplinary-team input and admission rates were evaluated for all new patient referrals from April 1 st to May 31 st 2019 (pre-pandemic) and compared to April 1 st to May 31 st 2020 (during-pandemic). This service evaluation project was approved by the local Research and Innovation Office. Results: There was a 37.7% reduction in the number of new patient referrals for 2020 compared to 2019, p < 0.00; Geriatric medicine referrals reduced by 46.5%, emergency department referrals reduced by 61.5%; community referrals increased 15-fold[AL1]. There were no differences in patients referred in terms of gender (p = 0.069), mean age (80.9(SD7.6) vs 79.1(SD6.6), p = 0.092), median conditions (5(IQR3.75–7) vs 6(IQ4–8), p = 0.329) and median medications (8(IQR5–11) vs 8 (IQR5.25–9), p = 0.600). Those referred pre-pandemic were frailer according to the clinical frailty score; median 5(IQR5–6) vs 5(IQR4–6), p = 0.013. In 2020, there was a significant reduction in referrals for physiotherapy (72.9% vs 37.3%, p < 0.001), occupational therapy (58.5% vs 37.8%, p = 0.005) and social work (47.5% vs 26.7%, p = 0.004). Clinical nutrition and speech and language remained the same, 16.1% vs 12%, p = 0.430 and 9.3% vs 12%, p = 0.552, respectively. In 2020, patients referred had significantly fewer attendances; median 4(IQR2–7) vs 3(IQR1–5), p = 0.002. There was no difference in admission rates between 2019 and 2020 (3.3% vs 7.9%, p = 0.149). Conclusion: During the COVID-Pandemic, the GDH evolved to provide more acute ambulatory medical care to avoid admissions. The GDH continues to adapt as the pandemic evolves and older adults needs change. Further comparative analysis will be required.